Search for the Standard Model Higgs Boson in the ZH -> v(v)over-barb(b)over-bar Channel in 5.2 fb(-1) of p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Amer Physical Soc, 2010)
A search is performed for the standard model Higgs boson in 5.2 fb(-1) of p (p) over bar collisions at root s = 1.96 TeV, collected with the D0 detector at the Fermilab Tevatron Collider. The final state considered is a pair of b jets and large missing transverse energy, as expected from p (p) over bar -> ZH -> v (v) over barb (b) over bar production. The search is also sensitive to the WH -> lvb (b) over bar channel when the charged lepton is not identified. For a Higgs boson mass of 115 GeV, a limit is set at the 95% C.L. on the cross section multiplied by branching fraction for [p (p) over bar -> (Z/W)H](H -> b (b) over bar) that is a factor of 3.7 larger than the standard model value, consistent with the factor of 4.6 expected.